Cambio social, criminalidad y control del crimen en Margarita (1960 - 1986) - Bravo Dávila, Luis A. (Colección estudios, 1993)
"Historical case study of Venezuelan Caribbean island of Margarita focuses on period 1960-86, 11 years previous to and 5 years following the year when island became a free trade zone. Charts demographic, economic, political, urban, and legal changes. Presents critical examination of official crime statistics, the criminal justice system, and the underground economy"--Handbook of Latin American Studies, v. 57